Extraction of Glycosaminoglycans Containing Glucosamine and Chondroitin Sulfate from Chicken Claw Cartilage - Tri Dewanti Widyaningsih; Widya Dwi Rukmi; Erni Sofia; Sudarma Dita Wijayanti; Novita Wijayanti; Rika Ersalia; Nia Rochmawati; Debora Nangin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2016)
Chicken cartilage (claw) is a waste of chicken cuts which are widely available in Indonesia. Cartilage part of chicken claw becomes a potential source of chondroitin sulfate (CS) and glucosamine (GS). This study aims to determine the most optimal extraction methods of CS and GS from cartilage of chicken claw. Various types of extraction methods used in this study are taken from the extraction by using boiling water (2 and 2.5 hours), acetic acid (7 and 17 hours), as well as proteolysis by papain (24 and 48 hours). Parameters observed include chemical characteristics of powdered cartilage of chicken claw as well as CS and GS levels in powdered cartilage of chicken claw extract. The results of this research show that the levels of CS and GS of chicken claw cartilage powder were 2.17% and 13%. Meanwhile, the highest GS level was obtained from the extraction with water treatment for 2.5 hours which was 8.1%. The treatment and duration of extraction will significantly affect the number of GS which was produced. The highest content of CS was obtained from the extraction with the enzyme treatment for 48 hours which was 2.47%. The best treatment is the extraction with water treatment for 2.5 hours which were the extracts with GS levels of 8.1% and 2.03% CS was selected through the analysis of multiple attribute.